Relation between self-determination and social skills in people with mild and moderate intellectual disability - Cvijetić, Marija M; Kaljača, Svetlana; Glumbić, Nenad (Specijalna edukacija i rehabilitacija, 2020)
Introduction. Self-determination of people with intellectual disability has been the subject of a large number of foreign studies in recent decades, while in our country this topic is insufficiently researched. Studies indicate that the manifestation of self-determined behavior can be influenced by various personal factors, including social skills. Objective. The aim of this study was to determine the significance of the relation between the level of self-determination in people with mild and moderate intellectual disability and their social skills. The sample included 128 subjects with mild and moderate intellectual disability, of both sexes, aged 21 to 58 years (M = 33.77, SD = 9.27). Methods. Self-determination was assessed using the Self-Determination Scale, while social skills data were collected using three subscales (the Socialization domain) of Vineland Adaptive Behavior Scale. Results. The results showed that persons with mild intellectual disability had a statistically significant higher overall level of self-determination and social skills, compared to persons with moderate intellectual disability. Statistically significant correlation between the level of self-determination and the level of social skills, observed through total scores on the used instruments, was found for the sub-sample of persons with moderate intellectual disability, but not for the sub-sample of persons with mild intellectual disability. Identified patterns of correlation between individual components of self-determination and domains of social skills indicated the specifics of the relation between these two concepts for each sub-sample. Conclusion. The obtained results indicate the need for detailed study of the levels and profiles of self-determination and social skills in persons with different levels of intellectual disability, as well as for careful interpretation of the correlation of the examined variables.
Keywords: self-determination; persons with mild intellectual disability; persons with moderate intellectual disability; social skills; choice